MILK PRODUCTION OF SHEEP AND LIVE WEIGHT GROWTH RATE OF LAMBS OF DIFFERENT BEHAVIORAL TYPES - Eshmuratova Sulukhan; Joldasbaeva Juldiz (Galaxy International Interdisciplinary Research Journal, 2023)
The article provides information about milk yield of sheep and growth of lambs of different behavioral types in pasture conditions, relation of growth rate of live weight of young animals of different behavioral types to their behavioral indicators.